2022
DOI: 10.1128/aem.00760-22
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Sequence (IS)-Excision Enhancer (IEE)-Mediated IS Excision from the lacZ Gene Restores the Lactose Utilization Defect of Shiga Toxin-Producing Escherichia coli O121:H19 Strains and Is Responsible for Their Delayed Lactose Utilization Phenotype

Abstract: Insertion sequences (ISs) can modulate gene expression by gene inactivation or activation. While phenotypic changes due to IS insertion/transposition are frequently observed, gene reactivation by precise or simple IS excision rarely occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…In conclusion, although initially described as common in E. coli O157:H7, our results show that IEE protein is highly conserved and shows a patchy distribution among EHEC, EPEC and ETEC/STEC genomes, suggesting not only promiscuous horizontal transfer across diverse E. coli serovars and phylogroups, but also a significant biological role in enhancing adaptability, as was recently proposed ( 11 , 13 ). Thus, IEE could be part of a generalized mechanism that supports adaptability to changing environmental conditions.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In conclusion, although initially described as common in E. coli O157:H7, our results show that IEE protein is highly conserved and shows a patchy distribution among EHEC, EPEC and ETEC/STEC genomes, suggesting not only promiscuous horizontal transfer across diverse E. coli serovars and phylogroups, but also a significant biological role in enhancing adaptability, as was recently proposed ( 11 , 13 ). Thus, IEE could be part of a generalized mechanism that supports adaptability to changing environmental conditions.…”
Section: Resultssupporting
confidence: 70%
“…Among them, the IS 3 family member IS 629 is the most abundant (23 copies) and is responsible for many polymorphisms associated with gene inactivation and/or genomic deletions ( 9 ). Detailed analysis of the transposition mechanism of IS 629 enabled the identification of a new protein, termed IS-excision enhancer (IEE), which promotes excision of IS 629 and other members of the IS 3 , IS 1 and IS 30 families in a transposase-dependent manner ( 10 , 11 ). The simultaneous presence of both IEE and IS 629 elements in almost all E. coli STEC strains from seropathotypes A and B, responsible for high pathogenicity and human disease, and the absence of at least one of them in the less pathogenic seropathotypes C and D, has led to the suggestion that their combined presence drives evolution towards increased virulence ( 12 ), which makes the study of this transposition system clinically important.…”
Section: Introductionmentioning
confidence: 99%
“…Although ISs are considered selfish genes, they can be utilized by different pathogens for the regulation of capsule production ( Acinetobacter baumannii (Whiteway et al , 2022)), for the regulation of metabolic pathways (Shiga toxin-producing Escherichia coli (Nakamura et al , 2022)) and the variation of O1 antigen ( Vibrio cholerae (Nesper et al , 2000)); however, how environmental factors regulate the excision of ISs is not well understood. For ixotrophy, our data suggest that the levels of available nutrients may regulate IS activity.…”
Section: Discussionmentioning
confidence: 99%
“…The co‐existence of IS 629 and the iee gene, which encodes IEE, may promote genomic diversity in enterotoxigenic E. coli (Kusumoto et al, 2014) and enhance the adaptability to environmental fluctuations in EHEC (Toro et al, 2015). IS excision can modify the phenotype of EHEC cultured under laboratory conditions (Kusumoto et al, 2001; Nakamura et al, 2022). It has also been reported that the combined activity of IS 3 and IEE enables the rapid formation of operons (Kanai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%